Histórias em quadrinhos na construção autobiográfica: reflexão sobre imagens - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The present work sought to investigate through the artistic practice of sequential art (Will Eisner, 1985) and the methodology of autobiografismo (Luciana Germano, 2022) teaching experiences. For data collection, a short course was held: Comics & Autobiography: Articulations between artistic practice and teaching, carried out with students of the Degree in Visual Arts at UNIFAP and a workshop at the Mário Quirino State School for 9th grade students. To think about the workshop and the initial training, the Triangular Proposal (Barbosa, 1991) was activated, which made it possible to think and articulate the knowledge in three axes: See (research artists who thematize comics in their practices), Contextualize (reflect on the teaching visual arts in contemporary times) and doing (practicing and controlling the poetics of the mini-course and workshop participants). The of this research point out that it is possible to think of didactic-artistic strategies involving autobiografismo and comics in the teaching of Art in schools and in the initial training of teachers of Visual Arts, I also emphasize that knowing about oneself in a perspective of experimentation of the practice artistic, enhances teaching knowledge and moves to think more creatively and reflect on Art/Education.
Keywords: Histórias em Quadrinhos; Autobiografismo; Arte-educação; Prática pedagógica; CNPQ::LINGUISTICA, LETRAS E ARTES::ARTES; ODS 4 – Educação de qualidade